Emissão de Compostos Orgânicos Voláteis (COVs) por Bacillus sp. no antagonismo a fitopatógenos da bananeira (Musa spp.) - Santos, João Evangelista de Ávila dos (2023)
Species of the genus Bacillus are important biocontrol agents for several phytopathogens that inhabit the soil and the postharvest phase of fruits, through the emission of volatile organic compounds (VOCs). Thus, the study of the antagonistic effect of Bacillus sp. isolated from the rhizosphere of banana trees (Musa spp.), against phytopathogens that attack its root system (Fusarium kalimantanense) and fruits (Lasiodiplodia brasiliensis and Colletotrichum musae), aiming to identify VOCs with antifungal activity. In total, 98 strains of rhizobacteria from banana trees were isolated and identified from various locations in the states of Ceará and Rio Grande do Norte - Brazil. The bacterial isolates were subjected to in vitro antagonist activity screening against the phytopathogen F. kalimantanense LPPC130. Among the active bacteria, Bacillus sp. LPPC170 showed promising results and was selected as an antagonist for co-cultivation experiments against L. brasiliensis and C. musae. The analysis of VOCs from microorganisms in axenic culture (Bacillus sp., F. kalimantanense, L. brasiliensis and C. musae) and from co-culture experiments (Bacillus sp. versus F. kalimantanense; Bacillus sp. versus L. brasiliensis, Bacillus sp. versus C. musae) were performed using combined techniques of headspace solid-phase microextraction (HS-SPME), gas chromatography coupled to mass spectrometry (GC/MS), and treatment of the results by multivariate analysis of data. Structural characterization was carried out by comparing fragmentation data from the obtained chromatograms, retention times, and Kovats indices of VOCs with data from the literature. The chemometric tool allowed the discrimination of the profile of VOCs according to the co-culture experiment. The data obtained revealed that the antagonist bacteria influenced the metabolism of phytopathogens. Some VOCs with antifungal activity (butanoic acid, pentanoic acid and 3-methylbutanoic acid) were mainly produced by the antagonist when confronted with phytopathogens. Other compounds of the fungus suffered from changes in their relative abundance and had their production inhibited. Chemical standards of the identified VOCs were obtained and tested for their antifungal activity. The results revealed that the volatile organic compounds emitted by Bacillus sp. LPPC170 were promising in inhibiting the mycelial growth of the phytopathogens analyzed and demonstrated their potential as possible biological control metabolites of banana diseases.